EFFECTS OF COOPERATIVE LOAN UTILIZATION ON ARABLE CROPS PRODUCTION AMONG COOPERATIVE FARMERS IN EGBEDA LOCAL GOVERNMENT AREA OF OYO-STATE, NIGERIA - Shittu, K.A.; Badejo, A.O.; Moore, N.C. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined effects of cooperative loan utilization on arable crops production among cooperative farmers in Egbeda Local Government Area of Oyo-State, Nigeria. Multistage random sampling technique was adopted to select 120 cooperative farmers. Data were obtained through structured interview schedule and analysed using descriptive and inferential statistics. Majority (80% and 87.5%) of the respondents were males, married with an average age and household size of 37 years and 5 persons, respectively. Adjusted R2 of arable crop output estimated at 80%, and off farm income, credit availability, distance to credit institution, credit size and interest on loan had significant relationship with cooperative loan utilization by arable crop farmer. Various constraints faced by farmers on arable crops' output includes: risk rationed (2.470), societies rules and norms (2.429), payment plans (2.458), price rationed without credit (2.425), quantity rationed (2.470), price rationed with (2.402), complicated procedures (2.395), response to credit (2.389), among others. The study concludes that off farm income, credit availability, distance to credit institution, credit size and interest on loan were the factors influencing cooperative loan utilization by arable crop farmers in the study area. Also majority of arable farmers utilized the loan obtained from cooperatives for aricultural activities. Therefore, the study recommended that, farmers should be encouraged and educated to join cooperative in order to have access to credit for optimum arable crop production and credit delivery in cooperative must be quick, faster and timely to meet the farmers' purpose and credit official should help credit users (arable crops farmers) to overcome credit challenges faced by arable crops farmers' output.